Dynamic Analysis of the Relationship between Economic Growth and Carbon Emissions: A Nonlinear and Asymmetric Approach - Moustafa, Marwa Mohammed Ali; Alomran, Sara Omran (International Journal of Energy Economics and Policy, 2025)
The main objective of this study is to investigate the non-linear relationship between economic growth and carbon emissions. To examine the validity of the Environmental Kuznets Curve (EKC) hypothesis for the Kingdom of Saudi Arabia during the period 1970-2022 based on a bound test for cointegration using Nonlinear Auto Regressive Distributed Lag model NARDL to examine the existence of asymmetric effect between carbon emission as a proxy for environmental degradation and gross domestic product per capita as a proxy for economic growth. Our empirical results confirm the presence of cointegration among the variables. Furthermore, the EKC hypothesis is invalid for the Kingdom of Saudi Arabia in the long run. While positive shocks in economic growth cause a reduction in CO2 emission, adverse shocks in economic growth cause a decrease in CO2 emission. This does not imply an inverted U-shaped link between economic growth and CO2 emissions. Energy consumption, inflation, and trade openness significantly increase CO2 emissions. Our results also revealed that foreign direct investment substantially decreases carbon emissions. It is clear from the results that Saudi Arabia is actively embracing green technologies as part of Vision 2030. This vision involves decreasing energy-intensive industries, turning to renewable energy sources, and expanding the services sector.